Idealisme dan Dualisme Daur Ulang Sampah di Indonesia: Studi Kasus Kota Semarang - Rukuh Setiadi; Moh Nurhadi; Feri Prihantoro (School of Postgraduate Studies, Diponegoro Univer, 2020)
This study analyzes various regulations on urban waste management, with emphasis in recycling activities. How regulatory frameworks from the national level translates to the city level, and the extent of its implementation are examined through field observations in the city of Semarang as a case study. Based on the study of regulations and policy documents, this study suggests that recycling is found in various policy domains, not only those concerning waste management but also in the environment, industry, company’s limited liability and infrastructure domains. This study highlights two main problems in recycling namely: policy idealism and approach dualism. From these two basic problems, this study recommends a strategy for strengthening the capacity and collaboration of related parties as one of keys to increase the capacity of waste recycling, especially in urban areas in Indonesia. These five strategic priorities that city governments need to consider include: (i) the restructurization of Waste Bank and Temporary Disposal Site (TPS) 3R, (ii) the development of a better network with informal sector, (iii) improvement on the way city government maintain engagement with local community group, (iv) Closing the gap of waste recycling policy in which city government must catch up constantly with the ideal format of waste recycling system stipulated in the waste management law and regulations, and (v) Increasing gender inclusiveness in the waste bank organizations.